Application Of Artificial Intelligence (Ai) In Television Industry Management Strategy Using Grounded Theory Analysis: A Case Study On Tvone - Ridwan, Dadang; Heikal, Jerry (Jurnal Pendidikan Indonesia, 2023)
The television industry has undergone many changes over time, especially with ever-increasing technological advances. One technology that has had a significant impact on this industry is artificial intelligence (AI). The purpose of this research is to understand the application of artificial intelligence (AI) in the television industry management strategy with a case study on tvOne. This study utilised qualitative methods to understand and describe the situation that takes place in the research environment. The sample in this study were five respondents from tvOne’s top management. The analysis began with the coding stage of the data derived from the results of the interviews which had been transcribed into text using a grounded theory approach. The conclusion of this study is that the opportunity provided by AI for the television industry is content production. Opportunities for implementing AI technology at tvOne, through the integration of AI in content production, are directed at increasing the efficiency and quality of program production by utilising more sophisticated data analysis and automation. Then, the challenges faced in implementing AI in the television industry are resources. The challenge of implementing AI technology at tvOne is in terms of human resources and physical resources needed, which include the necessary technical expertise and the availability of adequate financial resources and infrastructure.